2016
DOI: 10.1186/s12883-016-0675-3
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase inhibitors do not alter the length of stay in nursing homes among patients with Alzheimer’s disease: a prospective, observational study of factors affecting survival time from admission to death

Abstract: BackgroundThe survival time in nursing homes (NHs) in Alzheimer’s disease (AD) might be affected by sociodemographic/clinical characteristics, rate of disease progression, and use of specific medications and community-based services. Whether different aspects of cholinesterase inhibitor (ChEI) therapy modify time spent in NHs is unclear. Therefore, we examined the relationship between these potential predictors and survival time in NHs.MethodsThis prospective, multicenter study of ChEI treatment in clinical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Our findings reflect an inherent limitation of the MMSE to detect longitudinal changes in short‐term intervals in patients with severe dementia, which has been also reported even in long‐term intervals when functional decline is examined . The absence of significantly detected changes for group 3 (neither in SMMSE nor in MMSE) could not be attributed to specific demographic characteristics of the sample (absence of age, gender, and educational differences among the 3 groups) and could be explained under the view of slow decline in milder dementia stages when treatment with cholinesterase inhibitors can be more effective . The fact that cognitive deterioration has been found to be slow during the early and very late stages of dementia and follow a more rapid decline during the middle stages further highlights the clinical usefulness of the SMMSE and renders it as a valuable candidate instrument to evaluate the effect of pharmacological and nonpharmacological interventions in future studies, since it was only with the use of the SMMSE that we were able to detect significant changes over a period of 6 months in patients initially scored on the 0 to 6 range of MMSE.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Our findings reflect an inherent limitation of the MMSE to detect longitudinal changes in short‐term intervals in patients with severe dementia, which has been also reported even in long‐term intervals when functional decline is examined . The absence of significantly detected changes for group 3 (neither in SMMSE nor in MMSE) could not be attributed to specific demographic characteristics of the sample (absence of age, gender, and educational differences among the 3 groups) and could be explained under the view of slow decline in milder dementia stages when treatment with cholinesterase inhibitors can be more effective . The fact that cognitive deterioration has been found to be slow during the early and very late stages of dementia and follow a more rapid decline during the middle stages further highlights the clinical usefulness of the SMMSE and renders it as a valuable candidate instrument to evaluate the effect of pharmacological and nonpharmacological interventions in future studies, since it was only with the use of the SMMSE that we were able to detect significant changes over a period of 6 months in patients initially scored on the 0 to 6 range of MMSE.…”
Section: Discussionsupporting
confidence: 52%
“…First, the SMMSE was shown to have good internal consistency, as well as high and educational differences among the 3 groups) and could be explained under the view of slow decline in milder dementia stages 40 when treatment with cholinesterase inhibitors can be more effective. [41][42][43] The fact that cognitive deterioration has been found to be slow during the early and very late stages of dementia and follow a more rapid decline during the middle stages 40 Overall, by first confirming the psychometric properties of the…”
Section: Discussionmentioning
confidence: 85%
“…The effect of ChEI use on survival has not been clearly elucidated, but the trend is for increased survival time. The treatment with cholinesterase inhibitors (higher doses and longer duration of treatment) was associated with longer survival and slower cognitive deterioration in a prospective multi-centre study of ChEI in the clinical practice comprising 1021 communitybased AD patients followed-up for up to 16 years [76]. Conversely, in a sub-cohort of 220 nursing home-based patients from the same multi-centre study, the use of ChEI did not alter survival time [77].…”
Section: Cholinesterase Inhibitor Use and Outcomesmentioning
confidence: 97%
“…The costs of NHs are predominantly funded by the social security system; the annual cost in 2016 was SEK 655,000 (USD ~80,800, EUR ~68,200) per care recipient [ 3 ]. Our group reported that on average, 72% (4.1 years) of the period from AD diagnosis to death was spent in NHs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%